A Case of Hyperammonemia Associated with High Dihydropyrimidine Dehydrogenase Activity. (19th April 2016) - Nagaharu, Keiki; Ikemura, Kenji; Yamashita, Yoshiki; Oda, Hiroyasu; Ishihara, Mikiya; Sugawara, Yumiko; Tamaru, Satoshi; Mizuno, Toshiro; Katayama, Naoyuki
Abstract : Over the past decades, 5-Fluorouracil (5-FU) has been widely used to treat several types of carcinoma, including esophageal squamous cell carcinoma. In addition to its common side effects, including diarrhea, mucositis, neutropenia, and anemia, 5-FU treatment has also been reported to cause hyperammonemia. However, the exact mechanism responsible for 5-FU-induced hyperammonemia remains unknown. We encountered an esophageal carcinoma patient who developed hyperammonemia when receiving 5-FU-containing chemotherapy but did not exhibit any of the other common adverse effects of 5-FU treatment. At the onset of hyperammonemia, laboratory tests revealed high dihydropyrimidine dehydrogenase (DPD) activity and rapid 5-FU clearance. Our findings suggested that 5-FU hypermetabolism may be one of the key mechanisms responsible for hyperammonemia during 5-FU treatment.